The influence of collagen fragments extracted from the antarctic region fish scales on obesity development - Nagirniak, O. Yu.; Raksha, N. G.; Savchuk, O. M.; Ostapchenko, L. I. (Ukrainian Antarctic Journal, 2016)
Collagen is the most abundant protein in vertebrates, which constitutes about 30% of the total proteins and has been widelyused in food, cosmetic, biomedical, and pharmaceutical industries. The conventional source of collagen is from bovine andpig. However, the outbreak of prion diseases, such as bovine spongiform encephalopathy, has resulted in anxiety among users of collagen derived from these land animals. Thus, there is need to find an alternative source of collagen. Fish is one of the candidate assuch alternative sources because fish is unlikely to be associated with prion diseases. In addition, their skin, bones, scales, are rich in collagen type I. A simple method has been used for the isolation of collagen from the Antarctic region fish scales. At first, the scales were solublized using acetic acid containing EDTA. Then the solublized collagen was precipitated by using NaCl. The results of sodium dodecyl sulfate polyacrylamide gel electrophoresis confirmed the purity of extracted collagen and showed that obtained collagen was composed of two different α-chains (αl and α2), which were in accordance with the type I collagen. β component was also found in lesser amounts in this collagen samples. Next, collagen samples were hydrolyzed with pepsin at 370C for 24 h. According to obtained results collagen was cleaved into low-molecular weight fragments and peptides with molecular weight ranging from 26 to 2 kDa. The effect of collagen fragments on obesity development was investigated using animal model of obesity. For this purpose, the rats were fed with a high-calorie diet, which consisted of a standard meal (60%), pork fat (10%), eggs (10%), sugar (9%), peanuts (5%), dry milk (5%) and sunflower oil (1%) for four weeks. After that the animals were orally administrated with marine collagen fragments each second day for five consecutive weeks. It was shown that treatment with collagen fragments led to decrease of body weight and body mass index of the animals, which were on high-calorie diet (HCD). Found changes could be result of decrease of food intake and increase of water intake in compare with the rats in HCD group.